Fun English with Games to Improve Competence Speaking English Students at SDIT Assalam Green School, Cileungsi, West Java - Solo, Lenny; A.E, Yon; Siahaan, Leroy; Franscy, Franscy; Hidayati, Dini; Chairiyani, Ika; Rusmiati, Yanti; Agustin, Iswandini (PT FORMOSA CENDEKIA GLOBAL, 2024)
Learning language will be easier to master when you are a child, but the current curriculum in Indonesia places English language lessons as additional content. So activities are needed to motivate children to learn English. This article aims to introduce English to elementary school students. In this activity, the service applies games to attract students' interest. The application of games is based on the consideration that children at this age still like to play and it will be easier to attract the attention of elementary school students through games. There were 150 community service participants at SDIT Assalam Green School with the theme. Fun English with Games. After this activity was carried out, information was obtained that 99.3% of students liked this activity, 96.6% stated that through game activities made students enthusiastic about learning English, 97.3% stated that this activity increased knowledge related to English, and 98.6% stated that this activity made students want to learn English. Thus it can be concluded that there is an increase in English language knowledge obtained by students at SDIT Assalam Green School.